HANNIBAL’S REVENGES IN THOMAS HARRIS’ HANNIBAL RISING (2006) A PSYCHOANALYSIS APPROACH - Abu Fanani Fanani; Eka Putra Meizy Wahyuria Wahyuria; Muhammad Thoriqussuud Thoriqussuud; Nur Mufid Mufid; Amiq Amiq (Teaching and General Education Studies, 2026)
This study is about revenges by whose relatives have been hurt by others in Thomas Harris' Hannibal Rising. Using psychanalysis theory referring to the id, ego, and superego and supported by close reading and dramatic and descriptive method, the study finds that the character shows his id by his anger, retaliation, and killing to his enemies. This study then seems to be a simple one,  however, learning deeply the previous studies, the study gives a remarkable finding that the previous studies concentrate on the dissatisfaction of the id leading to the anxiety, whilst, the study on the satisfaction of the id